Perbandingan Metode Ekstraksi Dengan Aktivitas Antioksidan Dan Penentuan Kadar Total Flavonoid Dan Fenolik Pada Daun Bawang Merah (Allium ascalonicum. L) - Maria Ulfah; Dwi Yuni Mufarikhah; Ranni Puji Astutik; Mutmainnah Mutmainah (Universitas Wahid Hasyim Semarang, 2024)
Different extraction methods can affect the extracted compounds as well as the levels of flavonoids and total phenolics in leek extract (Garlic shallots. L). The aim of the research was to compare various extraction methods (percolation, reflux, maceration, Soxhlet) with 70% ethanol solvent on the antioxidant activity and total flavonoid and phenolic content of shallot leaf extract. Extracts from the 4 extraction methods were subjected to phytochemical screening and tested for antioxidant activity using the DPPH method using the standard standard of vitamin C λ 516.5 nm and measurement of total phenolic and flavonoid levels using the standard standard of quercetin λ 430 nm and gallic acid λ 743 nm using UV-Vis Spectrophotometry. Nilai IC50 and total phenolic and flavonoid levels were analyzed using independent One Way Anova and T tests. The research results show that leek extract contains phenolic compounds, flavonoids, tannins, saponins and alkaloids and has strong antioxidant activity in the percolation, reflux and maceration methods with IC50 values 88.12±0.78; 95.09±1.11; 99.39 ± 0.49 ppm and soxhlet 105.08 ± 0.39 ppm in the medium category and have a total phenolic content of 179,708 ± 0.42; 137.625 ± 0.42; 83,875 ± 0.42 and 69,708 ± 0.42 mgGA/g extract and total flavonoid content of 3,745 ± 0.02; 3,528 ± 0.02; 2,935±0.02 and 1.47±0.02 mgQE/g extract. Tukey analysis results showed significant differences (P<0.05) in antioxidant activity and total flavonoid and phenolic levels in the 4 extraction methods with the best order of percolation, reflux, maceration and soxhlet.